The present and future of production of green hydrogen, green ammonia, and green E-Fuels for the decarbonization of the Planet from the Magallanes region, Chile - Cacciuttolo, Carlos (2025)
The Magallanes region, in southern Chile, is positioned as a strategic hub for the production of green hydrogen (GH2), green ammonia, and synthetic fuels, thanks to its exceptional wind potential and commitment to sustainability. This article analyzes the opportunities and challenges of these energy vectors in the context of global decarbonization, highlighting the key role of the Magallanes region in the energy transition. Green hydrogen production, through wind-powered electrolysis, takes advantage of the region’s constant, high-speed winds, enabling competitive, low-emission generation. In turn, green ammonia, derived from GH2, emerges as a sustainable alternative for the agricultural industry and maritime transport, while synthetic fuels (e-fuels) offer a solution for sectors that are difficult to electrify, such as aviation. The sustainability approach addresses not only emissions reduction but also the responsible use of water resources, the protection of biodiversity, and integration with local communities. The article presents the following structure: (i) introduction, (ii) wind resource potential, (iii) water resource potential, (iv) different forms of hydrogen and its derivatives production (green hydrogen, green ammonia, and synthetic fuels), (v) pilot-scale demonstration plant for Haru Oni GH2 production, (vi) future industrial-scale GH2 production projects, (vii) discussion, and (viii) conclusions. In addition, the article discusses public policies, economic incentives, and international collaborations that promote these projects, positioning Magallanes as a clean energy export hub. Finally, the article concludes that the region can lead the production of green fuels, contributing to global energy security and the fulfillment of the Sustainable Development Goals (SDGs). However, advances in infrastructure, regulation, and social acceptance are required to guarantee a balanced development between technological innovation and environmental conservation.